Interpretação do gráfico de Hingle através de rede competitiva angular - SILVA, Carolina Barros da (Universidade Federal do Pará, 2014)
Water saturation is an important petrophysical property for formation evaluation, defining the final wellbore destination. The Archie’s equation calculates the water saturation for clean formations in function of rock resistivity, from a deep resistivity log and porosity, from one porosity log. The Archie’s equation, still involves the knowledge of formation water resistivity, which requires local determination and appropriated Archie’s coefficients. Hingle plot is traditional method in well logging for water saturation calculus, specially when the water resistivity is unknown. This method promotes a linearization of Archie’s equation from resistivity and porosity logs as the water line in the Hingle plot. The water resistivity is obtained from water line inclination. Independent of logging tools and digital computers development, the log analyst still handles with visual data interpretation and as all visual data interpretation, the Hingle plots interpretation is subject of sharpness errors. The objective of this dissertation is to simulate the visual interpretation of Hingle plot by a angular competitive neural network to mitigate the occurrence of sharpness errors and produces a real time first approach of water saturation, based on angular pattern identification in the raw well logging data.. The evaluation of this methodology is accomplished on synthetic data that satisfies the Archie’s equation and on actual well logging data.